Attencion to the health of tuberculosis patients: performance of the Community Health Agent: integrative review (Research, Society and Development, 2022)
Objective: To highlight the importance of community health agents in the care of tuberculosis patients. Methodology: This is an integrative literature review. The literature research was performed in the following scientific databases: Scientific Electronic Libary Online (Scielo), Virtual Health Library (VHL) and Google Scholar. Results: Regarding the primary care of tuberculosis patients, 12 articles were selected, these been published between 2017 to 2020, it was found that 8 articles addressed the topic in question and these were chosen as the source of research. Conclusion: It can be inferred that the contribution of the community health agent in monitoring and promoting the health of tuberculosis patients is indispensable, from the approach, identification, monitoring of treatment, showing that it is in agreement with the literature discussed. The many existing difficulties reveal that there is a lot to be done and that investment in knowledge and actions need to be emphasized, demanding attention and dedication from professionals facing this pathology.